2016
DOI: 10.1515/jcim-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

DLBS3233, a combined bioactive fraction of Cinnamomum burmanii and Lagerstroemia speciosa, in type-2 diabetes mellitus patients inadequately controlled by metformin and other oral antidiabetic agents

Abstract: BackgroundDLBS3233, a combined bioactive fraction of Cinnamomum burmanii and Lagerstroemia speciosa, has preclinically demonstrated its beneficial effects on glucose and lipid metabolism through the upregulation of insulin-signal transduction. This study evaluated the clinical efficacy of an add-on therapy with DLBS3233 in type-2 diabetes mellitus subjects inadequately controlled by metformin and other oral antidiabetes. MethodsThis was an open and prospective clinical study for 12 weeks of therapy, involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…DLBS3233 did not adversely affect body weight, liver, and renal function. Most adverse events observed were mild and they all had been resolved by the end of the study [77].…”
Section: Antidiabetic Hypolipidemic and Antiobesity Effectsmentioning
confidence: 91%
“…DLBS3233 did not adversely affect body weight, liver, and renal function. Most adverse events observed were mild and they all had been resolved by the end of the study [77].…”
Section: Antidiabetic Hypolipidemic and Antiobesity Effectsmentioning
confidence: 91%
“…DLBS3233 did not adversely affect body weight, liver, and renal function. Most adverse events observed were mild and they all had been resolved by the end of the study [58][59].…”
Section: Lagerstroemia Speciosamentioning
confidence: 93%
“…6 DLBS3233, an Indonesian herbal product, which is a combined bioactive fraction of Cinnamomum burmanii and Lagerstroaemia speciosa, has demonstrated benefits in glucose control and upregulation of insulin signal transduction. [7][8][9][10][11][12] Studies on Swiss Albino 3T3 pre-adipocytes mice showed that DLBS3233 works by increasing the expression of PI3-kinase, Akt, GLUT-4, peroxisome proliferators-activator receptor (PPAR)-γ, and PPAR-δ, and decreased the expression of the resistin gene at the mRNA level. 12 Previous in vitro studies also reported that DLBS3233 increased GLUT-4 expression leading to increased glucose uptake in insulin-resistant 3T3-Swiss Albino adipocytes.…”
Section: Introductionmentioning
confidence: 99%